Portrayal of Woman in Beer advertising in Kosovo (Case of PEJA Beer): Array - Sinani, Resul; Matoshi, Erzë (Acta Universitatis Danubius. Communicatio, 2020)
Beer advertising is often criticized for representing male protagonists in a leading and dominant role in relationship to women, introducing the female figure according to gender stereotypes. In such stereotyping, the woman is reduced to a sexist object of seduction. In order to investigate how the female figure is portrayed in the advertisements of the largest beer company in Kosovo, PEJA Beer, this paper examines the content of its advertisements. From the analysis of the advertising content that appeared on television between 2008 and 2019, we found that the man appears in the leading and dominant role whereas the woman is often presented through gender stereotypes. The research results show that there are more cases of advertisements in which there is no participation of women. In fact, only one advertisement is realized with a female protagonist. However, the perception to the female as an object of seduction and sexuality is extended in this advertisement. Therefore, the paper argues the hypothesis that the advertising of PEJA beer adopts gender stereotyping: The man adopts the dominant role with the woman in the background and portrayed as a temptation object with sexist elements.